Analisis Bibliometrika Produktivitas Dosen Universitas Udayana Pada Jurnal Terindeks SINTA 1, 2 dan Scopus - Suhartika, I Putu; Punia, I Nengah; Haryanti, Ni Putu Premierita (BACA: Jurnal Dokumentasi dan Informasi, 2024)
Research on bibliometric analysis in determining writer productivity has been widely carried out. However, this research is about joint work or collaboration among the authors, either as first author or as members (second, third author, and so on). Bibliometric analysis in this research is used only to analyze the productivity of the first author in individual and collaborative work in national journals indexed by SINTA 1, 2, and Scopus. This research uses quantitative methods based on bibliometric studies. Data processing uses documentation and literature studies, namely by collecting all the writings of Udayana University lecturers as first or sole authors within 10 years from 2013 to 2022, which are indexed by SINTA 1, 2, and Scopus. All of this data is processed and analyzed using Lotka Laws, one of the bibliometric studies used to measure author productivity. With this analysis, it is hoped that the productivity of Udayana University lecturers with publications indexed by SINTA 1, 2, and Scopus can be known. The research results show that the productivity of Udayana University lecturers as first authors in SINTA 1, SINTA 2, and Scopus-indexed journals is still low. In addition, the distribution of observation results shows that Dmax is greater than the critical value, so there is a significant difference between the distribution of observation results and the theoretical distribution of Lotka's Law. Therefore, the Udayana University lecturer article dataset does not follow Lotka's Law. This research can be used as material for making policy related to publications by Udayana University lecturers in reputable national and international journals